2019
DOI: 10.1111/pde.13751
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical treatment for hemangiomas

Abstract: Objective To quantify complications and rates of adverse events associated with surgical excision of hemangiomas in children using a national surgical database. Data source Pediatric American College of Surgeons (ACS) National Surgical Quality Improvement Program® (ACS NSQIP®‐pediatric), years 2012‐2016. Methods Subjects included children under 18 years with a postoperative diagnosis of International Classification of Diseases (ICD), 9th revision code: 228.00 and 228.01, or ICD 10 codes D18.00 and D18.01—heman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In a retrospective study of 1180 patients who had surgical excision of heamangiomas, the post operative complications were very minor and considerably low [19]. Thus surgical excision is the treatment of choice for recurrent heamangiomas or those refractory to nonoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 1180 patients who had surgical excision of heamangiomas, the post operative complications were very minor and considerably low [19]. Thus surgical excision is the treatment of choice for recurrent heamangiomas or those refractory to nonoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, for some IH children with vascular malformations and skin scars and even ineffective outcomes and relapse after drug treatment, surgical resection may be an alternative treatment because of its short treatment period, rapid lesion removal, and significant improvement in the appearance of the lesion site. Cheng et al (140) conducted a quantitative analysis of the incidence of complications and adverse events in 1,180 IH children (median age, 3.2 years) with surgical resection of the hemangiomas. The results suggested that surgical resection may be a safe treatment approach for patients with ineffective outcomes and incomplete treatment.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Recognition of vascular tumors such as IH is crucial because they are the most common tumor of infancy [ 1 ]. While IH can be life threatening, the majority of these lesions resolve on their own [ 2 ]. The difficulty lies in the fact that there is no reliable method for determining which lesions will spontaneously resolve and which lesions will need intervention.…”
Section: Introductionmentioning
confidence: 99%